Intestinal Dysbiosis and Biotin Deprivation Induce Alopecia through Overgrowth of Lactobacillus murinus in Mice - Atsushi Hayashi; Yohei Mikami; Kentaro Miyamoto; Nobuhiko Kamada; Toshiro Sato; Shinta Mizuno; Makoto Naganuma; Toshiaki Teratani; Ryo Aoki; Shinji Fukuda; Wataru Suda; Masahira Hattori; et al. (Cell Reports, 2017)
Metabolism by the gut microbiota affects host physiology beyond the gastrointestinal tract. Here, we find that antibiotic-induced dysbiosis, in particular, overgrowth of Lactobacillus murinus (L. murinus), impaired gut metabolic function and led to the development of alopecia. While deprivation of dietary biotin per se did not affect skin physiology, its simultaneous treatment with vancomycin resulted in hair loss in specific pathogen-free (SPF) mice. Vancomycin treatment induced the accumulation of L. murinus in the gut, which consumes residual biotin and depletes available biotin in the gut. Consistently, L. murinus induced alopecia when monocolonized in germ-free mice fed a biotin-deficient diet. Supplementation of biotin can reverse established alopecia symptoms in the SPF condition, indicating that L. murinus plays a central role in the induction of hair loss via a biotin-dependent manner. Collectively, our results indicate that luminal metabolic alterations associated with gut dysbiosis and dietary modifications can compromise skin physiology.